Conciliation in the administrative recourses during Revision of the Code of Canon Law. Analysis of the legislative works on the can. 1733 - Jałbrzykowski, Zbigniew (Prawo Kanoniczne, 2018)
The article deals with the history of redaction of the can. 1733 of the Code of Canon Law, which has introduced into the ecclesiastical legal order the institution of conciliation/mediation in hierarchical recourses. The norm attires attention because of its relatively innovative character in the catholic Church law. It makes part of a group of canons of the Latin Code that exhort to solve legal controversies in a non-contentious way or «pacifice» or through an «aequa solutio». The newness of the conciliation in the ecclesiastical context hasn’t contribute to its success, it is relatively hardly known and applied in the resolution of administrative controversies. The main point is that the new institution has been poorly harmonized within the procedural context of the hierarchical recourse. From the acts of the Pontifical Commission for the Revision of the Code of Canon Law follows that the conciliation in hierarchical recourses wasn’t made subject of an orderly and profound reflection during the legislation process. At the beginning it hadn’t even appear to the legislators as a possible procedural alternative to the regular administrative recourse. Next, borrowed from the report On due process, a document approved by the U.S. Conference of Bishops, the conciliation was incorporated into the system of ecclesiastical administrative justice among some doubts and unsure ideas about its purpose and systemic position, as it seems from the legislative documentation. With the expulsion of the administrative tribunals in limine promulgationis its function and mode of implementation has become even more obscure. As a result, a fruit of uncertainty and uncoordinated amendments in the legislation process, the conciliation recommended by the can. 1733 is made an institution to the greatest extent inoperative.